EMPOWERING WOMEN WORKERS IN KRETEK AND BEEDI INDUSTRIES: LEGAL REFORMS FOR SAFETY, EQUALITY, AND ECONOMIC JUSTICE - Pratama, Toebagus Galang Windi; Pathak, Gaurav; Widodo, Wahyu; Budoyo, Sapto (Faculty of Law, Universitas Diponegoro, 2025)
This study examines the socio-economic and health challenges faced by female workers in the Kretek and Beedi industries in Indonesia and India, respectively. These industries, while culturally significant, involve labor-intensive processes that predominantly employ women in rural areas. However, the working conditions are hazardous, exposing workers to respiratory illnesses, musculoskeletal disorders, and chronic diseases, compounded by low wages and insufficient labor protections. This research highlights the disparity in regulatory frameworks between the two industries, with Indonesia’s Kretek industry benefiting from better safety standards compared to the informal Beedi sector. Despite the challenges, both industries contribute significantly to the local economy, particularly through the employment of marginalized women. The study proposes policy reforms that aim to improve occupational safety, wage equality, and social security for female workers, ensuring their economic and social empowerment. Recommendations include strengthening labor laws, formalizing employment structures, and offering skill development and healthcare initiatives. By creating a protective legal environment and prioritizing gender equality, this research calls for collaborative efforts from governments, industries, and NGOs to foster a sustainable, inclusive future for these workers. The findings emphasize the urgent need to balance cultural preservation with worker welfare, ensuring long-term stability for both sectors.